Network analysis of work-family support and career identity and their associations with job burnout among primary healthcare workers: a cross-sectional study - Si-cheng Liu; Yuan Xu; Ming Yang; Jia-yi Sun; Qi-rong Qin; Qi-rong Qin; Qi-rong Qin; Gui-xia Fang; Gui-xia Fang (Frontiers in Public Health)
ObjectiveTo explore the complex associations between job burnout, career identity, and work-family support among primary healthcare workers from a network perspective.MethodsData were sourced from primary healthcare institutions in China’s central provinces. We used the Maslach Burnout Inventory Comprehensive Survey, a career identity scale tailored for primary healthcare workers, and the Chinese version of the Work-Family Support Questionnaire. A Gaussian network model was used to identify key factors, with “central nodes” being those that strongly influence others and “bridge nodes” connecting different parts of the network.ResultsOf the 8,135 participants surveyed, 5,120 (62.9%) reported job burnout. Compared to those with burnout, the non-burnout group scored higher in career identity, family support, and work support (54.29 vs. 49.42; 71.58 vs. 61.26; 35.03 vs. 31.20; p < 0.001). Network analysis revealed structural differences in the burnout-support-identity networks between groups after propensity score matching (M = 0.261, p < 0.001). In both groups, “understanding of role, content and requirements” were central nodes, while “work and family support” served as bridge nodes. Burnout was closely related to work support, family support, job suitability, and media criticism.ConclusionTargeting central and bridge nodes can help reduce job burnout among primary healthcare workers.